2005
DOI: 10.1164/rccm.200406-735oc
|View full text |Cite
|
Sign up to set email alerts
|

Airway Responses to Aerosolized Brevetoxins in an Animal Model of Asthma

Abstract: Florida red tide brevetoxins are sodium channel neurotoxins produced by the dinoflagellate Karenia brevis. When aerosolized, the toxin causes airway symptoms in normal individuals and patients with airway disease, but systematic exposures to define the pulmonary consequences and putative mechanisms are lacking. Here we report the effects of airway challenges with lysed cultures of Karenia brevis (crude brevetoxin), pure brevetoxin-2, brevetoxin-3, and brevetoxin-tbm (brevetoxin-2 minus the side chain) on pulmo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
123
1
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(134 citation statements)
references
References 41 publications
7
123
1
3
Order By: Relevance
“…tential for clearing mucus from the lungs, brevenal has been suggested as a potential treatment for cystic fibrosis (10). By manipulating the growth conditions for this alga through relatively simple salinity changes, we have shown that the yield of brevenal can be greatly enhanced.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…tential for clearing mucus from the lungs, brevenal has been suggested as a potential treatment for cystic fibrosis (10). By manipulating the growth conditions for this alga through relatively simple salinity changes, we have shown that the yield of brevenal can be greatly enhanced.…”
Section: Discussionmentioning
confidence: 89%
“…In sheep, picomolar levels of brevenal have been shown to alleviate the bronchial constriction and wheezing response to brevetoxin (10). Because of the po- Brevetoxin cell quota increased rapidly within <3 h after hypoosmotic stress and reached a plateau after 24 h that continued to day 6, with a decrease noted at day 67.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…25 Importantly, it has been reported that brevenal signi cantly improves tracheal mucus velocity at picomolar concentrations in an animal model of asthma, making this substance a potential lead for the development of novel therapeutic agents for the treatment of mucociliary dysfunction associated with cystic brosis and other lung disorders. 26 More recently, Mattei and co workers reported that brevenal is a potent inhibitor of catecholamine secretion induced by ciguatoxin without affecting other secretagogue activities, such as nicotine or barium induced secretion of catecholamine. 27 These results suggest brevenal has potential as a naturally occurring potent inhibitor of ciguatoxin induced neurotoxic effects and for treatment of ciguatera seafood poisoning.…”
Section: Total Synthesis and Structure Revision Of ( ) Brevenalmentioning
confidence: 99%
“…In addition to the marine organisms and coral reefs, even the HAB toxins themselves may be of future therapeutic value for humans (Burja et al, 2001;Abraham et al, 2005). Finally, the marine animals themselves may serve as alternative models of human diseases and human physiology (such as the sea slug, aplysia, and the elucidation of the processes of memory).…”
Section: Brief Introductionmentioning
confidence: 99%